2018
DOI: 10.1039/c8cp02662a
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalytic studies on imidazolium based ionic liquids: defining experimental conditions

Abstract: The number of publications devoted to studying electrochemical reactions in room temperature ionic liquids (RTILs) is constantly growing, but very few of them have been devoted to defining proper experimental conditions to obtain reproducible electrochemical results. In this work, we demonstrate that the combination of a proper RTIL purification treatment and a filtered Ar gas stream allow us to obtain featureless voltammograms in [C4mim][BF4], [C4mim][NTf2], and [C4m2im][NTf2], which otherwise present signals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 43 publications
1
28
0
Order By: Relevance
“…Prior of usage the as received [EMIM][DCA] electrolyte (>98 %, Iolitec, Germany) was cleaned by adding molecular sieve (3 Å, 400 mg/mL) and heated to 80 °C under vacuum (10 −3 mbar), as described previously . [EMIM][BF 4 ] (>98 %, Iolitec, Germany), [BMIM][BF 4 ] and [OMIM][BF 4 ] (99 %, Iolitec, Germany) were cleaned by stirring under vacuum . The resulting residual water concentrations were 31 mM for [EMIM][DCA], 50 mM for [EMIM][BF 4 ] and [BMIM][BF 4 ] and were measured by Karl‐Fischer titration.…”
Section: Methodsmentioning
confidence: 99%
“…Prior of usage the as received [EMIM][DCA] electrolyte (>98 %, Iolitec, Germany) was cleaned by adding molecular sieve (3 Å, 400 mg/mL) and heated to 80 °C under vacuum (10 −3 mbar), as described previously . [EMIM][BF 4 ] (>98 %, Iolitec, Germany), [BMIM][BF 4 ] and [OMIM][BF 4 ] (99 %, Iolitec, Germany) were cleaned by stirring under vacuum . The resulting residual water concentrations were 31 mM for [EMIM][DCA], 50 mM for [EMIM][BF 4 ] and [BMIM][BF 4 ] and were measured by Karl‐Fischer titration.…”
Section: Methodsmentioning
confidence: 99%
“…Several other studies have confirmed that the presence of water enhances the CO2RR in RTILs [8,10,21,[26][27][28]. This is not surprising because most pathways of the CO2RR require transfer of protons as well as electrons, and water is a good proton donor.…”
Section: What Is the Mechanism Accounting For The Reduced Overpotential?mentioning
confidence: 80%
“…(iii) Experimental work with single-crystal electrodes in RTILs aimed at understanding the role of surface structure and surface composition. This is a formidable challenge, due to the need of ultraclean conditions when working with this kind of electrodes and the well-known presence of impurities in RTILs [21,45,46], the levels of which can vary from one batch of product to the next. An additional problem in the case of neat RTILs is the absorption of water (from the atmosphere or from a gas being bubbled through the liquid), which acts as an impurity and can obscure relevant voltammetric features [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 72 , 73 These results, together, strongly support the formation of very strong catalytic acid sites in the water microdroplets of the more hydrophilic [bmim][BF 4 ] IL. 74 It must be noted here that the high density of water microdroplets in the IL significantly increases the surface area of the IL in contact with water, since a simple calculation leads to a value of 480 m 2 ·mL –1 of IL ( Figure S32 ). This result suggests that the increase in surface could also be behind the enhanced catalytic activity.…”
Section: Resultsmentioning
confidence: 95%